2021
DOI: 10.1038/s41598-021-97752-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia increases KIAA1199/CEMIP expression and enhances cell migration in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterised by dense desmoplasia and hypoxic microenvironment. Our previous reports demonstrated that hyaluronan (HA), especially low-molecular-weight HA, provides a favourable microenvironment for PDAC progression. However, the effect of hypoxia on HA metabolism remains unknown. Using quantitative real-time RT-PCR and western blot analysis, we analysed the changes in the expression of HA-synthesizing enzymes (HAS2 and HAS3) and HA-degrading enzymes (HYAL1, KIAA1199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…For example, EGFR activating mutations as in frame deletions in exon 19 or the Leu858Arg (L858R) point mutation in exon 21 are related with the therapeutic effect of first generation quinazoline reversible EGFR tyrosine kinase inhibitors (TKIs) in NSCLC patients. KIAA1199 mutation in the GG domain was reported to cause hearing loss due to the folding change of protein structure [ 13 ], meanwhile its carcinogenic effect was thought to be related to the overexpression of KIAA1199 [ 17 , 20 ], suggesting that KIAA1199 gene copy number amplification is responsible for the malignant progression of LUAD. However, whether other gene alteration types, such as missense mutations, are involved in the malignant progression of LUAD is still unknown and needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, EGFR activating mutations as in frame deletions in exon 19 or the Leu858Arg (L858R) point mutation in exon 21 are related with the therapeutic effect of first generation quinazoline reversible EGFR tyrosine kinase inhibitors (TKIs) in NSCLC patients. KIAA1199 mutation in the GG domain was reported to cause hearing loss due to the folding change of protein structure [ 13 ], meanwhile its carcinogenic effect was thought to be related to the overexpression of KIAA1199 [ 17 , 20 ], suggesting that KIAA1199 gene copy number amplification is responsible for the malignant progression of LUAD. However, whether other gene alteration types, such as missense mutations, are involved in the malignant progression of LUAD is still unknown and needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…KIAA1199, also known as cell migration inducing protein (CEMIP) or hyaluronan binding protein (HYBID), was reported to cause non-syndromic hearing loss and depolymerize hyaluronic acid (HA) [12,13]. In recent years, welldocumented studies have demonstrated that KIAA1199 plays a role in promoting malignant progression and predicts poor prognosis of cancer patients, including gastric cancer [14][15][16], pancreatic cancer [17], colorectal cancer [18,19], prostate cancer [20,21] and so on. Studies have shown that KIAA1199 can promote sorafenib tolerance and the metastasis of hepatocellular carcinoma [22], facilitate extracellular matrix-detached prostate cancer cell survival by inhibiting ferroptosis [23] and accelerate metastasis in other tumors [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The CEMIP locus is further surrounded by four T-cell factor 4 (TCF4)–binding sites, reflecting the fact that CEMIP is a target of the Wnt signaling pathway [ 6 , 47 , 48 ]. It also contains a hypoxia response element, consistent with the increased CEMIP expression observed under low-oxygen conditions through the stabilization of hypoxia-inducible-factor-2α (HIF-2α) [ 17 , 49 ]. The basic promoter activity of CEMIP is also regulated by DNA methylation and in human breast cancer hypomethylation correlates with high CEMIP expression [ 10 , 44 ].…”
Section: Regulation Molecular Architecture and Cellular Distribution ...mentioning
confidence: 92%
“…CEMIP-enhanced cell migration requires endoplasmic reticulum (ER) localization, where it forms a stable complex with the chaperone binding immunoglobulin protein BiP [ 29 ]. Hypoxia stimulates CEMIP-dependent motility in colorectal and PDAC cancer cells [ 17 , 49 ]. Furthermore, CEMIP induces invasion in NSCLC and ovarian cancer cells in a manner that is associated with the increased expression of PI3K and AKT [ 19 , 74 ].…”
Section: Cemip Functions and Their Relevance For Tumor Growth And Met...mentioning
confidence: 99%
“…In addition to activating HIF-1α signal, hypoxia also has other different effects. For example, hypoxia induces the expression of hyaluronic acid synthase and reduces the synthesis of hyaluronic acid degrading enzymes, resulting in high hyaluronic acid concentrations in hypoxia environments ( 38 ). Based on this phenomenon, a recent study used nanosystems to remotely enhance hyaluronidase activity, promote hyaluronic acid degradation, and reduce HIF-1α expression, alleviating the immunosuppressive tumor microenvironment ( 39 ).…”
Section: Glucose Metabolism In the Tumor Microenvironmentmentioning
confidence: 99%